Bahasa Inggris - Rafa Anugrah Putri; Parno; Ahmad Taufiq (Jurnal Penelitian Pendidikan IPA, 2025)
Students' scientific reasoning ability in physics learning remains a significant challenge. This study aims to evaluate the effectiveness of innovative learning models in improving students' scientific reasoning based on indicators such as control, correlation, probability, deductive hypothesis, and conservation. The method used is systematic literature review with PRISMA framework. The results showed that innovative learning models, such as Problem-Based Learning, Project-Based Learning, and Inquiry-Based Learning, have a positive impact on students' scientific reasoning. However, each model has weaknesses in improving certain indicators, especially probability and deductive hypothesis. Therefore, this study recommends the development of a learning model that integrates an authentic problem-based approach with STEAM and cognitive conflict strategies to improve students' scientific reasoning. This research provides insights for educators and researchers in designing more effective and relevant learning strategies.